Review Of The Emotional Disorder Theories In The Developmental Stage Of Adolescence. - Zeb, Aurang (International Journal of Rehabilitation and Special Education (IJRSE), 2021)
Emotions almost rule lives in every state of age, the difference  is that of level of control which is highly effected by the  situation faced by the individual. Emotions appear from the  physiques of the individuals unintentionally. Adolescence is  the most particular stage of life in which emotions develop  positively or negatively. It is a descriptive study for which the  primary data was collected from the research works of  theorists. The different aspects of emotional disorders and  disturbance in adolescence were reviewed and suggestions  were given. All the stake holders i.e. School, parents and  community around the developmental stage of adolescence are  beneficiary of it. The study suggests emotional disorder is the  combination of so many symptoms of emotional disturbance  which spoils life, if not find in time, ignoring or mishandling it.  Children in adolescence easily accept ecological effects,  positive effects develop sound mind and negative drags  towards negative impulses. There should be a balance and  proper mechanism for class promotion, award distribution and  other assignments of responsibilities among students so as to  create a positive environment in school.
Keywords: Adolescence; Emotions; Emotional disorder; Emotional disturbance; Anxiety; Depression; obsessive compulsive disorder